Localization of the motor neuron somata of geniohyoid muscle in rat: A horseradish peroxidase study - Aimi Nadia, Razlan; Muzammil, Ullah; Marina Yurievna, Kapitonova; Norhayati, Binti Liaqat Ali Khan; Syed Baharom, Syed Ahmad Fuad (World Association of Veterinary Anatomists, Wiley, 2018)
Aimi Nadia Binti Razlan1 | Muzammil Ullah1 | Marina Yurievna Kapitonova2 | Norhayati Binti Liaqat Ali Khan1 | Syed Baharom Syed Ahmad Fuad3